POLYTECHNIC LEARNERS’ PERCEPTION ON PRONUNCIATION ACQUISITION VIA QUESTIONNAIRE ADMINISTRATION TODAY - Kim, Regina Lim; Azmi, Mohd Nazri; Teh, Kamarul Shukri (PEOPLE: International Journal of Social Sciences, 2017)
his study examines perceptions of learners on pronunciation acquisition, learning phonetic transcriptions and their sounds associations amongst Polytechnic Kuala Terengganu Learners. This study was carried-out amongst semester one diploma of Electronics and Electrical Engineering learners in Kuala Terengganu Polytechnic, Terengganu, Malaysia. This study also hopes to show that by learning to recognise and read phonetic symbols learners will be able to overcome any pronunciation disability using the dictionary. This research follows the quasi- experimental design of a control-group A and treatment group B selected randomly doing a pre-test and post-test. The treatment of explicit instruction of phonetic transcriptions for 45 hours was given only to the experimental group. This study focuses on the analysis of oral test answers by learners. Some of the challenges identified in the acquisition of pronunciation are mother tongue interference, mispronunciation because spelling does not reflect pronunciation, unintelligibility and miscommunication and the lack of confidence to speak the English Language. Whilst factors that affect pronunciation acquisition are mother tongue, exposure, motivation, students’ perception, ways of learning, which English to speak and others. However, it was discovered that phonetic instruction of transcriptions and their sounds’ association improves pronunciation competence. Some of the implications of this study are aimed at ELT academicians and practitioners to apply the method used in this study to up-grade the standard of pronunciation proficiency and a suggestion that the learning of pronunciation using phonetic symbols should be taught earlier in their education.